2021
DOI: 10.1213/ane.0000000000005839
|View full text |Cite
|
Sign up to set email alerts
|

Airway Ultrasound as Predictor of Difficult Direct Laryngoscopy: A Systematic Review and Meta-analysis

Abstract: BACKGROUND: Despite several clinical index tests that are currently applied for airway assessment, unpredicted difficult laryngoscopy may still represent a serious problem in anesthesia practice. The aim of this systematic review and meta-analysis was to evaluate whether preoperative airway ultrasound can predict difficult direct laryngoscopy in adult patients undergoing elective surgery under general anesthesia. METHODS: We searched the Medline, Scopus, and Web of Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 73 publications
3
28
0
Order By: Relevance
“…This analysis showed that compared to other major predictors studied in recent literatures [ 5 , 7 , 40 , 41 , 42 ], TMHT had a satisfying predictive potential for DL with stability, comprehensiveness and independence. A systematic review and meta-analysis on various airway ultrasound predictors, such as the distance from skin to epiglottis (DSE), the distance from skin to hyoid bone (DSHB), and the distance from skin to vocal cords (DSVC), showed that DSE was the best imaging predictor, with a sensitivity of 82% (95% CI, 74–87%), a specificity of 79% (95% CI, 70–87%), and an AUC of 87% (95% CI, 84–90%) [ 40 ]. As patients with a history of previous difficult intubation or expected difficult laryngoscopy have been excluded from the above analysis of airway ultrasound predictors, the overall quality of evidence is low/very low and there is a high concern of bias [ 40 ].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This analysis showed that compared to other major predictors studied in recent literatures [ 5 , 7 , 40 , 41 , 42 ], TMHT had a satisfying predictive potential for DL with stability, comprehensiveness and independence. A systematic review and meta-analysis on various airway ultrasound predictors, such as the distance from skin to epiglottis (DSE), the distance from skin to hyoid bone (DSHB), and the distance from skin to vocal cords (DSVC), showed that DSE was the best imaging predictor, with a sensitivity of 82% (95% CI, 74–87%), a specificity of 79% (95% CI, 70–87%), and an AUC of 87% (95% CI, 84–90%) [ 40 ]. As patients with a history of previous difficult intubation or expected difficult laryngoscopy have been excluded from the above analysis of airway ultrasound predictors, the overall quality of evidence is low/very low and there is a high concern of bias [ 40 ].…”
Section: Discussionmentioning
confidence: 66%
“…The prediction of difficult airways has always been a crucial task for anesthesiologists in terms of airway management. Systematic reviews have been performed on various preoperative assessment methods, but inconsistent conclusions have been drawn [ 40 , 41 , 42 ]. According to the summary estimates of our review and analysis, the overall predictive value of TMHT for DL seems optimistic, with a sensitivity of 74%, a specificity of 88%, and an AUC of 85%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound can be used to identify anatomical landmarks of the upper airway and for accurate measurements. Carsetti et al [ 16 ] pointed out that upper airway ultrasound may be a powerful tool for improving the performance of difficult airway management predictive tests, providing an objective assessment of specific index tests and thus restricting the interobserver variability. The current guidelines for preprocedural evaluation recommend using a combination of the validated tests to predict, and thereby, manage difficult airways, because no factor can provide an accurate prediction when assessed alone.…”
Section: Discussionmentioning
confidence: 99%
“…The distance from the epiglottis to the midpoint of the distance between the vocal folds (E-VC) [ 20 ].…”
Section: Technical Aspects Of An Airway Ultrasoundmentioning
confidence: 99%